Determinasi Kepemimpinan, Kompetensi dan Beban Kerja Melalui Job Stress terhadap Kinerja Perawat Rumah Sakit Santa Elisabeth di Kota Batam - Sianturi, Sahat Parlindungan; Wibisono, Chablullah; Satriawan, Bambang (Universitas Batanghari Jambi, 2025)
This study aims to examine the determination of leadership, competency and workload through job stress on the performance of nurses at Santa Elisabeth Hospital in Batam City. The design used in this research is a quantitative approach, the population in the study is 278 people and the sample is 164 people, the questionnaire is distributed via a Google Form link with an estimate of data collection for one month, after the data is collected it will then be processed and analyzed further. The research results show that leadership and competence have no significant effect on job stress. Meanwhile, job stress, leadership, competency and workload have a significant effect on nurse performance. Meanwhile, job stress does not interfere with the influence of leadership, competence and workload on nurse performance. The magnitude of the influence of leadership, competence and workload on job stress is 46.8%. Meanwhile, leadership, competence and workload on performance are 54.1%.